Comparative immunophenotyping of equine multipotent mesenchymal stromal cells: An approach toward a standardized definition. Issue 8 (3rd June 2014) - Paebst, Felicitas; Piehler, Daniel; Brehm, Walter; Heller, Sandra; Schroeck, Carmen; Tárnok, Attila; Burk, Janina
Abstract Horses are an approved large animal model for therapies of the musculoskeletal system. Especially for tendon disease where cell‐based therapy is commonly used in equine patients, the translation of achieved results to human medicine would be a great accomplishment. Immunophenotyping of equine mesenchymal stromal cells (MSCs) remains the last obstacle to meet the criteria of the International Society for Cellular Therapy (ISCT) definition of human MSCs. Therefore, the surface antigen expression of CD 29, CD 44, CD 73, CD 90, CD 105, CD 14, CD 34, CD 45, CD 79α, and MHC II in equine MSCs from adipose tissue, bone marrow, umbilical cord blood, umbilical cord tissue, and tendon tissue was analyzed using flow cytometry. Isolated cells from the different sources and donors varied in their expression pattern of MSC‐defining antigens. In particular, CD 90 and 105 showed most heterogeneity. However, cells from all samples were robustly positive for CD 29 and CD 44, while being mostly negative for CD 73 and the exclusion markers CD 14, CD 34, CD 45, CD 79α and MHC II. Furthermore, it was evident that enzymes used for cell detachment after in vitro‐culture affected the detection of antigen expression. These results emphasize the need of standardization of MSC isolation, culturing, and harvesting techniques. As the equine MSCs did not meet all criteria the ISCT defined for human MSCs, further investigations for a better characterization of the cell type should be conducted. © 2014 International Society for Advancement of Cytometry